New age of money transfer: CBDCs - Babir, Guliyev (Dunakavics, 2024)
This paper provides a comprehensive analysis of Central Bank Digital Currencies (CBDCs), examining their potential to transform the global financial landscape. It explores the three primary models of CBDC issuance: direct, indirect, and hybrid, detailing their operational complexities, privacy concerns, financial inclusion potential and regulatory challenges. The study also delves into cross-border CBDC initiatives, assessing various models for enhancing payment system interoperability and cooperation among central banks. Additionally, the paper addresses critical issues such as cybersecurity risks and privacy implications associated with CBDCs, emphasizing the need for robust regulatory frameworks and technological safeguards. Overall, the findings highlight the promising yet complex role of CBDCs in improving transactional efficiency, expanding financial access, and reinforcing monetary security in an increasingly digital economy.